The Role Placental TLR-7 Expression with Cord Blood HBV DNA and Placental HBV DNA: Peran Ekspresi TLR-7 Plasenta dengan HBV DNA Tali Pusat dan HBV DNA Plasenta - Naeny Fajriah; Maisuri T. Chalid; Lenny Lisal; Efendi Lukas; St. Nur Asni; Rina Masadah (Indonesian Socety of Obstetrics and Gynecology, 2022)
Abstract Objective: To determine the role of TLR-7 expression on intrauterine vertical transmission in pregnancy through identification of serum hepatitis B markers in both maternal and umbilical cord blood. Methods: Analysis of TLR expression was performed on 38 paraffin block samples of placental tissue acquired from mothers with HBV using TLR immunohistochemical staining. Results: 16 of 38 samples were acquired from mothers aged 26-30 years-old. Most of the samples were from primiparous mothers (52.6%). This study found no significant association between TLR-7 expression and HBV DNA in the placenta and cord blood (p = 1.000). However, we found a significant association between placental TLR-7 expression and maternal HBV DNA (p = 0.034). Meanwhile, placental HBeAg and HBV DNA were not associated with placental TLR-7 expression (p = 0.082; p = 1.000). Conclusion: There was no significant association between TLR-7 expression and HBV DNA in the placenta and cord blood, but we found a significant association between TLR-7 expression and maternal HBV DNA. Keywords: HBV DNA, Hepatitis B, intrauterine infection, placental toll-like receptor (TLR) 7,umbilical cord. Abstrak Tujuan: untuk melihat peran ekspresi TLR-7 terhadap transmisi vertikal intrauterina pada kehamilan melalui identifikasi marker serum hepatitis B pada darah ibu dan talipusar. Metode: Analisis ekspresi TLR dilakukan pada 38 sampel blok paraffin jaringan plasenta ibu yang menderita HBV dengan memakai pewarnaan imuhohistokimia TLR. Hasil: 16 dari 38 sampel berusia 26-30 tahun. Sebagian besar sampel merupakan kelompok primipara (52.6%). Penelitian ini tidak menemukan hubungan yang signifikan antara ekspresi TLR-7 di plasenta dan HBV DNA darah tali pusat (p = 1.000). Tapi, kami menemukan hubungan yang signifikan antara ekspresi TLR-7 plasenta dan HBV DNA ibu (p = 0,034). Sedangkan HBeAg dan HBV DNA plasenta tidak berhubungan dengan ekspresi TLR-7 plasenta (p = 0,082; p = 1.000). Kesimpulan: Tidak ada hubungan yang signifikan antara ekspresi TLR-7 dan DNA HBV di plasenta dan tali pusat, tetapi kami menemukan hubungan yang signifikan antara ekspresi TLR-7 dan DNA HBV ibu. Kata kunci: HBV DNA, Hepatitis B, infeksi intrauterina, plasenta, tali pusat, toll-like receptor (TLR) 7